A survey of recycling behaviour in households in Dhaka, Bangladesh - Rafia, Afroz; Hanaki, Keisuke; Tuddin, Rabaah; Ayup, Kartinah (sage publication, 2010)
This paper examines the factors that might influence recycling behaviour of the households in Dhaka city, Bangladesh. Information on recycling activity, socio-economic characteristics, and attitudes of the households towards recycling were obtained from interviews with 456 households in Dhaka. Logistic regression analysis was used to determine the dominant factors that might influence the recycling behaviour of the households. The results showed that environmental consciousness, the availability of storage space, and age (25–35 years) are significant positive predictors of recycling behaviour (at the 1% level). Another variable Income 2 (TK3,000–15,000) is also positively correlated with recycling (at the 5% level).Establishment of a recycling programme could be an effective strategy in implementing sustainable waste management in Bangladesh. For this strategy to succeed, however, active partnership between households and the waste management service department is required. The households’ attitudes toward recycling should, therefore, be taken into consideration as should the results of this study, which are important indicators of households’ positive attitudes toward sustainable waste management in Dhaka.